Kohéziós kihívások a V4 országok fejlődésében - Veres, Lajos (Acta Scientiarum Socialium, 2015)
Cohesion Challenges in the Development of Visegrad 4 Countries.The development cohesion of V4 countries concerns in a number of external and internal impacts. External factors stands out among East-West intermediate position resulting from the geopolitical situation. In Central and Eastern Europe, the V4 countries established an exemplary cooperation in the recent years in the Ukrainian-Russian war, as well as in the treatment of "migrant" issue. This study does not deal with these topics, but also focus on internal issues of social and economic cohesion, examine the relationship between economic performance, competitiveness, innovation, logistics performance and corruption. The author proposes the development of a potential field of cohesion force in the V4 countries.
Keywords: competitiveness; innovation; logistics performance; corruption; cohesion spaces